2004
DOI: 10.1002/cbdv.200490008
|View full text |Cite
|
Sign up to set email alerts
|

TMC‐95A Analogues with Endocyclic Biphenyl Ether Group as Proteasome Inhibitors

Abstract: TMC-95A, a cyclic tripeptide metabolite of Apiospora montagnei, is a potent competitive inhibitor of proteasome. Based on the X-ray structure of its complex with yeast proteasome, the synthetically challenging structure of this natural product was simplified in a first generation of analogues by replacing the highly oxidized side-chain biaryl system with a phenyl-oxindole group. In the present study, the TMC-95 biaryl group was substituted with a biphenyl ether with retainment of significant proteasome inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 52 publications
1
34
1
1
Order By: Relevance
“…Compared to the previously reported noncovalent macrocyclic peptide BIA-1a (Figure 1), the covalently binding macrocyclic aldehydes reported here are 1000-fold more potent. 17,23 In addition to being the first macrocyclic peptide aldehydes with specificity for the proteasome, we found that introduction of a macrocycle significantly increases selectivity for the proteasome over intracellular cysteine proteases, such as calpains and cathepsins.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared to the previously reported noncovalent macrocyclic peptide BIA-1a (Figure 1), the covalently binding macrocyclic aldehydes reported here are 1000-fold more potent. 17,23 In addition to being the first macrocyclic peptide aldehydes with specificity for the proteasome, we found that introduction of a macrocycle significantly increases selectivity for the proteasome over intracellular cysteine proteases, such as calpains and cathepsins.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 90%
“…22 In accordance with previously synthesized biaryl ether analogues of TMC-95A, a modified Phe at P 4 and Tyr at P 2 were used to generate the ether macrocycle. 23 Leu was selected for the P 1 position based on the peptide sequence of carfilzomib and MG-132 and is thought to form favorable interactions with Met45 in the S 1 pocket of the β5 subunit. 24 The P 3 position was varied between two hydrophobic residues, Leu and Phe(OMe).…”
mentioning
confidence: 99%
“…3a) [41]. In these compounds, a biphenyl ether clamp has been used to preorganize the peptide backbone into an extended -sheet conformation.…”
Section: Biphenyl Ethersmentioning
confidence: 99%
“…Another key structural modification was disclosed by the Moroder group in 2004 [22]. Considering that the role of the phenoleoxindole biaryl system in TMC-95 is to induce and stabilize an extended b-type peptide backbone conformation, which is mandatory for optimal interaction with the proteasome, they planned to replace this complex framework by an endocyclic biaryl ether.…”
Section: Moroder's Tmc-95a Analoguesmentioning
confidence: 99%